Pengaruh Net Working Capital, dan Debt to Asset Ratio Terhadap Cash Holding Pada PT Indofood CBP Sukses Makmur TBK Periode 2011 – 2020 - Jepri Arizal; Amthy Suraya (Formosa Journal of Sustainable Research, 2022)
This research was conducted at PT. Indofood CBP Sukses Makmur Tbk which aims to find out Net Working Capital,and Debt to Asset Ratio at PT. Indofood CBP Sukses Makmur Tbk Period 2011-2020. The data used in this study is secondary data sourced from financial data of PT. Indofood CBP Sukses Makmur Tbk has been published through www.idx.com. The sample used in the study was 1 company registered with the IDX during the year 2011-2020. The data collection method in this study uses documentation methods, library studies and data recording from the company's financial statements for the period 2011-2020. Research methods use a Quantitative Descriptive approach as well as conducting classical assumption testing which includes, Normality Test, Multicollinearity Test, Heteroskedasticity Test autocorrelation and multiple linear regression test, hypothesis test (T and F) and coefficient of determination test. Based on the partial t test obtained the result of t calculated for Net Working Capital of  9,742 > 2,365  with Sig value. 0,000 < 0,05 which means there is a partial effect on the Cash Holding. And t calculate Debt to Asset Ratio of 2,886 > 2,365 with Sig value. by 0,023  < 0,05, which means that there is a partial influence on the Cash Holding in PT. Indofood CBP Sukses Makmur Tbk. period 2011-2020. Then for simultaneous F test results obtained f test results of  65,553 > 4,46 and Sig. value of  0,000 < 0,05, which means there is simultaneous influence  between Net Working Capital,and Debt to Asset Ratio to Cash Holding.